Effectiveness of discharge education on outcomes in acute coronary syndrome patients: a systematic review protocol. (April 2018) - Kourbelis, Constance; Franzon, Julie; Foote, Jonathon; Brown, Alex; Daniel, Mark; Coffee, Neil T.; Newman, Peter; Nicholls, Stephen; Clark, Robyn A.
Abstract : Review question: The question of this review is what is the effectiveness of discharge education on outcomes in acute coronary syndrome patients?